Dual-energy CT virtual non-calcium technique for detection of bone marrow edema in patients with vertebral fractures: A prospective feasibility study on a single- source volume CT scanner. Issue 87 (February 2017) - Diekhoff, T.; Hermann, K.G.; Pumberger, M.; Hamm, B.; Putzier, M.; Fuchs, M.
Abstract: Objectives: Dual-energy computed tomography (DECT) is a recent development for detecting bone marrow edema (BME) in patients with vertebral compression fractures. The aim of this pilot study was to determine the reliability of single-source DECT in detecting vertebral BME using magnetic resonance imaging (MRI) as standard of reference. Materials and methods: Nine patients with radiographic thoracic or lumbar vertebral compression fractures underwent both, DECT on a 320-row single-source scanner and 1.5 T MRI. Virtual non-calcium (VNC) images were reconstructed from the DECT volume datasets. Three blinded readers independently scored images for the presence of BME. Only vertebrae with loss of height in radiography (target vertebrae) were included in the analysis. A vertebra was counted as positive if two readers agreed on the presence of BME. Cohen's kappa was calculated for interrater comparison. Intervertebral ratios of target and the reference vertebra were compared for CT attenuation and MR signal intensity in a reference vertebra using Spearman correlation. Signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) were calculated. Results: Fourteen target vertebrae with a radiographic height loss were identified; eight of them showed BME on MRI, while DECT identified BME in 7 instances. There were no false positive virtual non-calcium images, resulting in a sensitivity of 0.88 (0.75–1.0 among all readers) and specificity of 1.0 (0.81–1.0). Interrater agreement was inferior for DECT (κ = 0.63–0.89) compared to MRI (κ = 0.9–1.0). Intervertebral ratio in VNC images strongly correlated with short-tau inversion recovery (r = 0.87) and inversely with T1 (-0.89). SNR (0.2 +/− 0.2 in VNC and 16.7 +/− 7.3 in STIR) and CNR (0.2 +/− 0.3 and 7.1 +/− 6.3) values were inferior in VNC. Conclusions: Detecting BME with single-source DECT is feasible and allows detection of vertebral compression fractures with reasonably high sensitivity and specificity. However, image quality of VNC reconstructions has to be improved to achieve better interrater agreement. Nonetheless, DECT might accelerate the diagnostic work-flow in patients with vertebral compression fractures in the future and reduce the number of additional MRI examinations.